2011
DOI: 10.1038/ki.2011.118
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and chronic kidney disease

Abstract: The incidence of malnutrition disorders in chronic kidney disease (CKD) appears unchanged over time, whereas patient-care and dialysis techniques continue to progress. Despite some evidence for cost-effective treatments, there are numerous caveats to applying these research findings on a daily care basis. There is a sustained generation of data confirming metabolic improvement when patients control their protein intake, even at early stages of CKD. A recent protein-energy wasting nomenclature allows a simpler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 111 publications
(146 reference statements)
5
123
0
14
Order By: Relevance
“…Considering the wide variety of Chinese food as well as poor accuracy of diet diaries recorded by patients, we used an alternative method instead of dietary interview to estimate phosphate intake (mg/d), which was equal to the protein intake (g/d) multiplied by 15 (mean 15 mg Pi/g protein) (15,16). The normalized protein equivalent nitrogen appearance (nPNA) was chosen as a surrogate of dietary protein intake (17,18).…”
Section: Assessment Of Phosphate Balance In Mhd Patientsmentioning
confidence: 99%
“…Considering the wide variety of Chinese food as well as poor accuracy of diet diaries recorded by patients, we used an alternative method instead of dietary interview to estimate phosphate intake (mg/d), which was equal to the protein intake (g/d) multiplied by 15 (mean 15 mg Pi/g protein) (15,16). The normalized protein equivalent nitrogen appearance (nPNA) was chosen as a surrogate of dietary protein intake (17,18).…”
Section: Assessment Of Phosphate Balance In Mhd Patientsmentioning
confidence: 99%
“…It has been previously postulated that a level lower than 15 mg/dl, and certainly lower than 11 mg/dl, significantly increases the prognostic risk and requires nutritional intervention and monitoring of prealbumin levels (24). Other authors cite a serum level below 30 mg/dl as suggestive for malnutrition in patients undergoing haemodialysis (25), while a large study identified that prealbumin levels less than 20 mg/dl in dialysis patients were associated with a higher death rate even in patients with normal albumin levels (26). One study found that serum prealbumin level of ≤20 mg/dl was found to determine increased risk for postoperative infections and need for longer intubation time in patients undergoing cardiac surgery (27).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, in patients who are pre-dialysis and treated by a maintenance method, a protein supply lower than 0.6 g/kg/day has been proposed in association with KAs supplementation (El Nahas & Coles, 1986). However, the risk of protein malnutrition, and the constraints inherent to this supplementation led to recommend a moderate dietary protein supply of about 0.8 g/kg/day (Klahr et al, 1994 ;Tom et al, 1995 ;Levey et al, 1996a;Dumler, 2011;Fouque et al, 2011a). In dialysis patients, the protein restriction question is more complex because there is a aggravated risk of protein-caloric undernutrition with an increased morbidity and mortality (30% of the dialysis patients) (Parker et al, 1983;Young et al, 1991).…”
Section: Present Dietary Approach To Treat the Patient With Chronic Rmentioning
confidence: 99%
“…This leads to a rejection of protein restriction with, as a result, a proposed supply in the 1 to 1.2 g/kg/day range (Bergström, 1995 ;Cianciaruso et al, 1995 ;Qureshi et al, 1998 ;Antunes et al, 2010). However, it is still uncertain whether this policy is enough in order to equilibrate the N balance in these patients since there is a proportional relationship between the protein supply and the rate of N catabolism as it is estimated by the PCR (protein catabolism rate) (Movilli et al, 1993 ;Harty et al, 1994;Fouque et al, 2011a). The protein-caloric undernutrition observed in dialysis patients is often linked to a deficient supply (Ikizler et al, 1995 ;Pollock et al, 1997, Kalantar-Zadeh, 2003, which is itself often linked to a depressed appetite (Bergström, 1995;Van Der Eijk & Farinelli, 1997).…”
Section: Present Dietary Approach To Treat the Patient With Chronic Rmentioning
confidence: 99%
See 1 more Smart Citation